Function and Mechanism of Trimetazidine in Myocardial Infarction-Induced Myocardial Energy Metabolism Disorder Through the SIRT1–AMPK Pathway - Luo, Xiu-ying; Zhong, Ze; Chong, Ai-guo; Zhang, Wei-wei; Wu, Xin-dong (Frontiers in Physiology, 2021)
Myocardial energy metabolism (MEM) is an important factor of myocardial injury. Trimetazidine (TMZ) provides protection against myocardial ischemia/reperfusion injury. The current study set out to evaluate the effect and mechanism of TMZ on MEM disorder induced by myocardial infarction (MI). First, MI mouse model was established by coronary artery ligation, which were then treated with different concentrations of TMZ (5, 10, 20 mg/kg/day). The results suggested that TMZ reduced heart/weight ratio in a concentration-dependent manner. TMZ also reduced levels of Bax and Cleaved Caspase-3 and promoted Bcl-2 expression. In addition, TMZ augmented ATP production and SOD activity induced by MI, and decreased the levels of LPO, FFA and NO in a concentration-dependent manner (all P < 0.05). Furthermore, H2O2-induced cell injury model was established and treated with different concentrations of TMZ (1, 5, 10 μM). The results showed that SIRT1 over-expression promoted ATP production and ROS activity, and reduced the levels of LPO, FFA and NO in H9C2 cardiomyocytes treated with H2O2 and TMZ. Silencing SIRT1 suppressed ATP production and ROS activity and increased the levels of LPO, FFA and NO (all P < 0.05). TMZ activated the SIRT1-AMPK pathway by increasing SIRT1 expression and AMPK phosphorylation. In conclusion, TMZ inhibited MI-induced myocardial apoptosis and MEM disorder by activation of the SIRT1-AMPK pathway.